How Do We Come to Know? Exploring Maple Syrup Production and Climate Change in Near North Ontario - Murphy, Brenda; Chrétien, Annette; Brown, Laura J. (Scholars Commons @ Laurier, 2009)
This paper reports on a pilot project exploring the impacts of climate change on maple syrup production in understudied near north, Ontario spaces. Maple syrup is produced by settler, Métis and First Nations communities for commercial distribution and as part of a mixed subsistence economy. The focus on maple syrup is opportune, since syrup production and sugar maple trees (Acer saccharum) are extremely susceptible to climate change and the biophysical and social impacts of climate change on maple syrup production in the near north of Ontario have yet to be understood. Given that the process of developing research is under-reported and that this project has had the opportunity to undertake a funded development process, this paper describes and assesses our process of ‘coming to know’, which has been guided by the following objectives: 1) to undertake an exploratory investigation of the nature of available data about long-term syrup production and climate change in both settler and Indigenous communities, 2) to include and valorize marginalized Indigenous voices and ecologies, 3) to focus on collecting climate change data from understudied near north spaces, 4) to assess the availability and quality of ecological and quantitative data in order to enhance locally-relevant understandings of climate change, and 5) to work towards the development of a cross-cultural and transdisciplinary methodological framework within which to accomplish the first four objectives. We approach these objectives across disciplinary boundaries and cultural perspectives, and with growing relationships with community partners. We describe the rich sources of information found through the pilot study and discuss highlights of our on-going process of developing our research project.